Exploring the Impacts of Slum Dwelling for Indian Women - Patel, Maya Laxmi (Université d'Ottawa / University of Ottawa, 2015)
Background: Urbanization is increasing around the world, and in India this trend has translated into an increase in the size of slum dwellings. Slum environments may have a negative effect on human health, in particular women’s health. The objective of the study is to determine factors associated with Indian women’s health in slum environments. Methods: The relationship between women’s health, measured by BMI, and demographic, behavioural, and socioeconomic factors was statistically modelled. A multiple linear regression was performed, using data from the India National Family Health Survey. Results: Increasing BMI is significantly and positively associated with: frequency of watching television, having diabetes, age, wealth index, and residency status in the areas of New Delhi, Andhra Pradesh or Tamil Nadu. Conclusion: While belonging to a scheduled tribe was not associated with changes in BMI, unadjusted rates suggest that tribal status may be worthy of deeper investigation. Among slum dwellers, there is a double-burden of under-nutrition and over-nutrition. Therefore a diverse set of interventions will be required to improve the health outcomes of these women.
Keywords: Slum dwelling; Women’s health; Indian women; Tribe in slums